Massacre at the Champ de Mars : popular dissent and political culture in the French Revolution - Andress, David, 1969- (Royal Historical Society : Boydell Press, 2000)
On 17 July 1791 the revolutionary National Guard of Paris opened fire on a crowd of protesters: citizens believing themselves patriots trying to save France from the reinstatement of a traitor king. To the National Guard and their political superiors the protesters were the dregs of the people, brigands paid by counter-revolutionary aristocrats. Politicians and journalists declared the National Guard the patriots, and their action a heroic defence of the fledgling Constitution.
Keywords: Louis -- XVI, -- King of France, -- 1754-1793 -- Flight to Varennes, 1791.; Bailly, Jean Sylvain, -- 1736-1793 -- Death and burial.; Bailly, Jean Sylvain, -- 1736-1793; Louis -- XVI, -- King of France, -- 1754-1793; Ludwig -- XVI. -- Frankreich, König -- 1754-1793; Bailly, Jean Sylvain -- 1736-1793; Ludwig (Frankreich, König, XVI.); Bailly, Jean Sylvain.; France -- History -- 1789-1793 -- Atrocities.; HISTORY.; HISTORY -- Modern -- General.; Death and burial of a person; Atrocities; France; Festnahme; Paris -- Marsfeld -- Massaker; Tod; Varennes-en-Argonne; Politieke situatie.; Oproeren.; Massamoorden.; Paris -- Marsfeld -- Massaker.; 1789-1793; Champ de Mars.; Corruption.; Counter-Revolutionary Aristocrats.; Jacobin Republic.; Massacre.; National Guard.; Parisians.; Patriotism.; Political Unanimity.; Treason.; History